Ocular syphilis in an immunocompetent host. (2020) - Roy, Moni; Roy, Ashish K.; Farrell, John J.
Abstract: Syphilis is an old disease that experienced a resurgence with the emergence of HIV/AIDS. Syphilis is a reportable infection that is monitored by the Centers for disease Control (CDC) in the U.S. and rates have been rising since 2000. Although ocular syphilis is a well known consequence of syphilis infection it continues to be less frequently diagnosed, partially because ocular manifestations are not reportable to CDC. While the majority of recent cases in the U.S. have been reported in men who have sex with men (MSM) population, 50 % of these cases are HIV negative. We present a case of acute iridocyclitis and ocular hypertension due to syphilis infection. This case reiterates the need to increase healthcare workers' awareness of the importance of timely recognition of potential ocular syphilis to prevent visual sequelae from the infection. Ocular syphilis should be kept in the differential diagnosis in immunocompetent/HIV negative patients, and the importance of obtaining a detailed sexual history should not be forgotten.